An economic analysis of public law Demos and Agora - Dellis, Georges (Cheltenham, UK Northampton, Massachusetts, USA Edward Elgar Publishing Limited, 2021)
This original and insightful book considers the ways in which public law, which emphasises legality (the Demos), and economics, a science oriented towards the markets (the Agora), intertwine. Throughout, George Dellis argues that the concepts of legality and efficiency should not be perceived separately."
Public law and economics : a necessary encounter -- What a lawyer needs to know about economics : a rational (?) eye on everything -- Economic analysis of public law : to the Coase theorem and beyond -- To be or not to be? : a general economic theory for public law : examining the benefits and costs of state intervention -- Principles and methods for increasing efficiency in public law -- Games of public power : what economics teaches us about constitutions -- Between freedom and paternalism : an economic analysis of fundamental rights and the limits of public intervention -- Modernising the Demos : institutional architecture and procedural mechanics in public law -- Economic analysis and the resolution of public law disputes : the scales, the sword and the blindfold of justice -- The ascent of a new and efficient public law.
Includes bibliographical references and index.
Keywords: Law and economics. -- Electronic book; Public law -- Economic aspects; Law and economics